Efficacy of the body mass reduction program in obese women in perimenopausal age in comparison with the efficacy of that program in obese women in 18–44 years of age - K. Karczewski, Jan; Ostrowska, Lucyna; M. Lech, Medard (Menopause Review/Przegląd Menopauzalny, 2002)
Design: Observational study of the group of obese patients recruited and treated in The Clinical Center for Cardiology and Body Mass Reduction in Białystok (eastern part of Poland). Material and methods: 12 months of clinical observation of the two groups of obese women, taking part in the special body mass reduction program; Group I – 81 women in perimenopauzal age, Group II – 107 women in 18–44 years of age. The proposed treatment contained diet, physical exercises, psychological support and pharmacotherapy. Results: The positive reaction for the treatment of obesity was less visible in obese women in perimenopauzal age, than in the group of obese women in 18–44 years of age. As it was observed, the worse reaction for the proposed treatment in the group of women in perimenopauzal age was not connected with lower BMR, than in the group of obese women in 18–44 years of age. Conclusion: Body mass reduction programs for women in perimenopauzal age should concentrate on building the motivation of the patients, and in most cases the result of treatment is related to possibility of reimbursement of the costs of treatment from the social security system.